Social Comparison in the Organization of the Structure of Self-Efficacy of Higher Education Students - Zavatskа Nataliia; Omelianiuk , Serhii; Lukashov , Oleksandr; Petrenko , Maksym (Insight: the psychological dimensions of society, 2024)
The aim of the empirical study was to determine the statistical reliability of social comparison in the organization of the structure of self-efficacy of higher education students. Methods. The study sample consisted of students from an educational institution who studied at three levels of academic programs on a full-time basis (n = 108). Descriptive frequency characteristics of the sample population: M = 21.35; 21.35; SD = ± 3.96; Мe = 21.50. А psychodiagnostic complex of methods that reflected relevant dimensions of the study was аpplied: “The Social Comparison Scale” (Schneider & Schupp, 2014); “The Self-Efficacy Scale” (Sherer et al., 1982); “Diagnostics of motivational structure of personality” (DMSP) (Milman, 1990). Additionally, the current average academic score of the students for the previous exam session was introduced. Results. Descriptive frequency characteristics of the investigated parameters were determined. A correlation matrix and a correlation pleiad of social comparison parameters with measurements of students’ self-efficacy were constructed. Nine direct statistically significant correlations were identified, demonstrating that “self-efficacy of interpersonal communication”, “communication”, and “general activity” of higher education students were capable of determining their self-efficacy in the context of academic and professional activities. It was stated that self-awareness of their abilities allows respondents to expand their cognitive component, positively affecting attitudes and the activity’s conative component. The comparison of groups with low and high indicators of the formation of social comparison proved that according to two parameters: “average academic score” and “self-efficacy of subject activity” of groups with high levels had significant superiority. Discussion and сonclusions. It was explained that the average score and self-efficacy in subject activities were the most operational and sensitive parameters in the context of social comparison. It was substantiated that research on social comparison within the organization of self-efficacy structure among higher education students was a socio-psychological validation complex for the educational and professional training of future specialists, which had a dual impact. It was noted that the identified regularities can be implemented in the organization of the educational process to enhance the self-efficacy of students.